Testing the adaptive nature of morphological diversification in the hemiparasitic genus Thesium L. (Santalaceae) - Moore, Timothy Eoin (Department of Biological Sciences, 2015)
This thesis tests the hypothesis that parasitism in Thesium represents a specialised foraging strategy for dealing with the nutrient poor soils found in the CFR.